Analysis of E-Government implementation in public services: study on personnel agency and human resource development in Banyumas Regency - Catur Lina Widiyanti (Gema Wiralodra, 2023)
The Banyumas Regency Government passed Regional Regulation No. 4 of 2012 concerning the Master Plan for E-Government Development in the Banyumas Regency. Banyumas Regency is the only district in Central Java with a regional regulation on E-Government and has received many awards in the field of Technology. This study aims to determine the implementation of E-Government at BKPSDM and the factors that support and hinder the implementation of E-Government at BKPSDM in Banyumas Regency. This research uses a descriptive qualitative method. The data analyzed in this study comes from primary data, namely informants as research objects are BKPSDM experienced in E-Government development, and secondary data, namely documents, relevant research results, journals, books, statistical data, and other sources. The data in this study were analyzed using triangulation techniques. The results of the study stated that the implementation of E-Government in personnel administration services at the Banyumas Regency Personnel and Human Resource Development Agency was quite good, as evidenced by the many programs that were targeted throughout the year and continued to develop at each stage. Factors supporting the success of E-Government implementation in Banyumas Regency are communication, for example, transmission, consistency, clarity of information, and adequate infrastructure resources. The obstacle they faced was that they were overwhelmed because of the small number of personnel in terms of technical personnel.